Media Pembelajaran Mata Pelajaran Bahasa Indonesia SD Di Era Digital - Puspita Sari, Esi (Pendidikan Dasar dan Manajemen Pendidikan, 2023)
Education is very important in the development of children`s knowledge and insight. Education is a conscious effort in the process of changing a person`s attitude, the knowledge possessed by each individual, both his knowledge and the things he does in his life to be better than his thoughts and attitudes through teaching and training efforts. Moreover, the education of elementary school-age children in this era of digital development. The developing digital era has indeed utilized in education as a means and infrastructure for pasticipation between teachers and students. Then social science is needed for students in social life and socializing as well as adapting to the surrounding environment. Moral attitudes need to be taught from an early age so that children can face the problems they will face later. The method in this study uses the library study method. Elementary Indonesian language subjects relate to 4 aspects, namely listening, speaking, writing and reading. Elementary school Indonesian language learning requires learning media that supports teaching and learning. Digital-based learning media can help teachers and facilitate student learning.